Promoting organic food products and exports: Status, issues and way forward - Arpita Mukherjee; Souvik Dutta; Souvik Mendiratta; Avantika Kapoor; Tanu M. Goyal (Indian Council for Research on International Economic Relations (ICRIER), 2017)
In recent years, the Indian Government has taken several policy initiatives to promote organic farming and organic food exports. Such measures are expected to enrich soil quality; attain sustainable development goals; ensure health and food safety for consumers; increase farmer's income and link them to the global markets; increase investment in organic food manufacturing and retailing, and create employment. A number of entrepreneurs have responded positively to government initiatives and several start-ups have been formed in the organic food segment. A number of conventional food manufacturers, retailers and exporters have diversified their businesses to include organic food products. Within the food processing segment, this is a fast growing sector with high growth potential and ability to create employment. This paper, based on a primary survey of companies engaged in organic food business in India and the United Kingdom (UK), examines how organic food can attract more investment (domestic and foreign) across the entire food supply chain including manufacturing, farming, distribution and trading if supported by the right policy. It also focuses on how companies in the organic food business are linked to farmers and how this linkage can be strengthened in order to enable farmers to have better access to the domestic and global markets. The paper identifies the issues and business risk that companies face and makes policy recommendations for enabling the holistic growth of this sector.
Keywords: C83; D22; Q15; Q22; 330; organic food; companies; policy; India; United Kingdom; survey